2018
DOI: 10.9734/ejmp/2018/38537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hippophae rhamnoides L. Leaf and Marc Extract with Reduced Tannin Concentration on the Health and Growth Parameters of Newborn Calves

Abstract: Aim: To study the effects of orally administered mixture of Hippophae rhamnoides leaf and marc extracts (HLM) on health parameters of newborn calves. Study Design: Starting from birth day 0 (D0) till day 15 (D15) the extract of HLM was given orally to newborn calves before feeding them milk at an increased dosage from 5 to 8 ml/calf/ two times a day for prophylaxis of nutritional diarrhoea. The calves were clinically examined and weighed. Biochemical and morphological analyses of blood were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
4
2
0
Order By: Relevance
“…Decreasing the number of days that calves experience diarrhoea, can reduce medical complications, thus involving fewer costs for the farmer and a better future performance (Lorenz et al 2011). These results were in line with findings reported in calves (Bonelli et al 2018;Liepa et al 2018;Gupta et al 2020) where the shortening of the diarrhoeic episode was found in tannin-treated patients. The lack of differences concerning the ADG between the two groups suggests that the tannin powder does not affect the animals' growth.…”
Section: Group Csupporting
confidence: 93%
See 4 more Smart Citations
“…Decreasing the number of days that calves experience diarrhoea, can reduce medical complications, thus involving fewer costs for the farmer and a better future performance (Lorenz et al 2011). These results were in line with findings reported in calves (Bonelli et al 2018;Liepa et al 2018;Gupta et al 2020) where the shortening of the diarrhoeic episode was found in tannin-treated patients. The lack of differences concerning the ADG between the two groups suggests that the tannin powder does not affect the animals' growth.…”
Section: Group Csupporting
confidence: 93%
“…Our findings could suggest an initial hepatocellular damage caused by the administration of chestnut tannins in calves, as already reported in calves (Wieland et al 2015). Despite the differences found between the two groups, the serum AST, ALB and GGT and blood methaemoglobin results fell within the normal range, confirming previous findings in neonatal calves (Liepa et al 2018). In our opinion, given an oral dose of 10 g/ calf q24h, of chestnut tannins could be a safe procedure for calves of up to two months old.…”
Section: Group Csupporting
confidence: 91%
See 3 more Smart Citations